2013
DOI: 10.1016/j.ajog.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

How do good candidates for trial of labor after cesarean (TOLAC) who undergo elective repeat cesarean differ from those who choose TOLAC?

Abstract: OBJECTIVE Our aim was to compare good candidates for trial of labor after cesarean (TOLAC) who underwent repeat cesarean to those who chose TOLAC. STUDY DESIGN Data for all deliveries at 14 regional hospitals over an 8-year period were reviewed. Women with a primary cesarean and 1 subsequent delivery in the dataset were included. The choice of elective repeat cesarean vs TOLAC was assessed in the first delivery following the primary cesarean. Women with ≥70% chance of successful vaginal birth after cesarean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 13 publications
3
57
3
Order By: Relevance
“…We found no national data on the number of TOLAC deliveries managed by CNMs, but our findings suggest that increasing opportunities for midwives to manage low‐risk TOLAC patients could be a safe and effective means to improve vaginal birth rates. A cultural and ideological shift toward offering TOLACs may be a notable obstacle; however, as fewer providers and hospitals are allowing TOLACs, some women may be unaware of the opportunity, and some reports suggest that fewer women overall are requesting VBAC . Our data were collected prior to the publication of specific guidelines to reduce primary cesarean birth .…”
Section: Discussionmentioning
confidence: 99%
“…We found no national data on the number of TOLAC deliveries managed by CNMs, but our findings suggest that increasing opportunities for midwives to manage low‐risk TOLAC patients could be a safe and effective means to improve vaginal birth rates. A cultural and ideological shift toward offering TOLACs may be a notable obstacle; however, as fewer providers and hospitals are allowing TOLACs, some women may be unaware of the opportunity, and some reports suggest that fewer women overall are requesting VBAC . Our data were collected prior to the publication of specific guidelines to reduce primary cesarean birth .…”
Section: Discussionmentioning
confidence: 99%
“…3 Metz et al, for example, have suggested provider factors are a potentially significant reason for disparities in rates of trial of labor after cesarean among women who are good candidates. 27 Similarly, Bernstein et al found when women with a prior cesarean perceived their provider to have a preference, they were more likely to choose their perceived provider-preferred delivery mode. 28 Patient preferences should be considered along with safety and medical capacity, and providers have a role in offering balanced counseling incorporating realistic framing of risks and benefits.…”
Section: Commentmentioning
confidence: 97%
“…Personal wishes of the pregnant woman and her partner would influence the decision to a great extent, as would the experiences of the counseling obstetrician and the traditions of the specific delivery ward. Metz et al [33] found that less than one third of women regarded as good candidates for TOL, (with a VBAC chance !70% using the Grobman model [8]), finally chose TOL. Bernstein et al [22] showed that candidates for TOL were poorly educated about risks and benefits associated with different delivery modes, and that the majority chose the delivery mode preferred by their care-provider.…”
Section: Commentsmentioning
confidence: 98%